A miniaturized multi‐wideband Quasi‐Yagi MIMO antenna system. Issue 5 (10th January 2018) - Jehangir, Syed S.; Sharawi, Mohammad S.
Abstract: A multi‐band directional multiple‐input–multiple‐output (MIMO) antenna system is presented based on a rectangular loop excited Quasi‐Yagi configuration. A 64% reduction in size is obtained using a rectangular meandered element as well as a small ground plane. The proposed two‐element MIMO antenna system covers the Telemetry L‐band and several LTE/WLAN bands. It has a wide measured bandwidth of 689 MHz (1.897–2.586 GHz) in the desired band centered at 2 GHz, and a measured bandwidth of more than 168 MHz across rest of the bands. The MIMO antenna system has a total size of 45 × 120 × 0.76 mm 3, with a single element size of 55 × 60 × 0.76 mm 3 . The non‐desired back‐lobe radiation which is obtained using a small ground plane, is significantly reduced by using a novel defected ground structure (DGS) as compared with the complex techniques present in literature. The proposed DGS provides a high measured front‐to‐back ratio of 14 dB at 2 GHz and 11 dB in other bands. A maximum measured realized gain of 5.8 dBi is obtained in the desired band using a single parasitic director element. The proposed MIMO antenna system has a minimum measured radiation efficiency of 70%, isolation of 12 dB, and envelope correlation coefficient of 0.098 within all bands which ensures very good MIMO performance.